Outcome and Prognostic Factors for Canine Splenic Lymphoma Treated by Splenectomy (1995–2011). Issue 8 (1st October 2015) - van Stee, Lucinda L.; Boston, Sarah E.; Singh, Ameet; Romanelli, Giorgio; Rubio‐Guzman, Alejandro; Scase, Tim J.
Abstract : Objective: To assess the outcome of canine splenic lymphoma treated with splenectomy and to evaluate prognostic factors, including involvement of other sites, adjuvant chemotherapy, and the effect of World Health Organization (WHO) histological classification of canine malignant lymphoma. Design: Multi‐institutional, retrospective study. Animals: Client‐owned dogs (n = 28). Methods: Medical records (1995–2011) of dogs with a histological diagnosis of splenic lymphoma and treated by splenectomy submitted by Veterinary Society of Surgical Oncology members were reviewed. Included were dogs treated with or without adjuvant therapy. Overall survival, disease‐free interval, and cause of death were determined. Prognostic factors and the WHO histological classification of canine malignant lymphoma were evaluated with respect to outcome. Results: Dogs with splenic lymphoma treated by splenectomy had a 1‐year survival rate of 58.8%, after which no animals died of their disease. B cell lymphoma held a better prognosis for survival than other variants of splenic lymphoma. Marginal zone lymphoma and mantle cell lymphoma were the most common B cell lymphoma subtypes in our study. Hemoabdomen and clinical signs related to splenic lymphoma, including abdominal distention, lethargy, and anorexia, were poor prognostic indicators, whereas disease confined to the spleen was a positive prognostic indicator. Pre‐ or postoperative adjuvant chemotherapy did not provide a survival benefit. Conclusion: Based on our sample population, splenectomy alone was an effective treatment for splenic lymphoma in cases with disease confined to the spleen. Chemotherapy may not improve survival in cases of lymphoma restricted to the spleen.